Characterizing the patchy appearance of the circumgalactic medium and the influence of foreground absorption - Ponti, G.; Sanders, J. S.; Locatelli, N.; Zheng, X.; Zhang, Y.; Yeung, M.; Freyberg, M.; Dennerl, K.; Comparat, J.; Merloni, A.; Di Teodoro, E.; Sasaki, Manami; et al. (Astronomy & Astrophysics, 2023)
Context. Recent studies have demonstrated that the emission from the circumgalactic medium displays a relatively high degree of patchiness on angular scales of a∼10. Aims. Taking advantage of the Spectrum Roentgen Gamma eROSITA Final Equatorial Depth Survey, we aim to constrain any variation in the X-ray surface brightness on scales ranging from sub-degrees to a hundred square degrees. Result. The surface brightness in the soft X-ray band (0.3-0.45 keV) shows modulations of about 60% on scales of several degrees. The amplitude of such variations decreases at higher energies. The observed patchiness is stable over a period of two years, therefore excluding the possiblity that it could have been induced by solar wind charge exchange. We also observe no correlation between such an excess and the density of galaxies in the Local Universe, suggesting no strong contribution from the hot baryons in the filaments of the cosmic web. Instead, the soft X-ray emission is anti-correlated with the column density of absorbing material. Indeed, we can reproduce the spectrum of the bright and dark regions by simply varying the column density of the matter absorbing the emission components located beyond the Local Hot Bubble, while no modulation of the intrinsic emission is required. At high Galactic latitudes, the eROSITA all-sky map shows patchiness of the soft X-ray diffuse emission similar to the one observed in the eFEDS field; it is therefore likely that the same"absorption-modulation" is present over the entire sky. Conclusions. The observed patchiness of soft X-ray diffuse emission within the eFEDS field is primarily a consequence of absorption. Our spectral decomposition of the soft X-ray background appears accurate, predicting that (apart from the Local Hot Bubble) all other spectral components are modulated by clouds beyond ∼200 pc from the Sun. These results highlight the importance of an accurate treatment of the absorption effects in determining the patchiness of the circumgalactic medium.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Galaxy: general; ISM: bubbles; ISM: structure; Local insterstellar matter; Solar wind; X-rays: diffuse background